Application Of Discipline In Forming Character In National Education Authorities East Oku District: Application Of Discipline In Forming Character In National Education Authorities East Oku District - Helisia Margahana (Institute of Computer Science (IOCS), 2020)
This study aims to analyze partially and jointly the effect of placement, work climate on employee productivity and to analyze the most dominant variables in influencing the work productivity of employees at the East OKU District National Education Office, the results of regression analysis and the correlation between job placement and work climate. employees show a regression model.